The Role of Attachment in Refugees with Impaired Mental Health: A Systematic Review - Thomas Egger; Anna Buchheim; Manuela Gander (Brain Sciences)
Although the relationship between attachment and mental health has been widely studied, no systematic review has focused specifically on refugee populations. Objectives: This systematic review examines associations between attachment patterns and psychological distress in refugees—a population at elevated risk for mental health disorders due to forced displacement and trauma. Methods: Following PRISMA guidelines. we searched PubMed, PsycINFO, and Web of Science (last search: 5 October 2024). Studies were included if they examined the relationship between attachment and psychological distress or disorders in refugees, presented empirical data, were peer-reviewed, were published from 2004 onward in English, and met quality criteria based on CASP and JBI checklists. Studies were excluded if they did not focus on refugees, lacked empirical data, did not assess both attachment and psychological distress, were not peer-reviewed, or consisted of grey literature. A narrative synthesis was conducted. Results: Of 2.951 records, 11 studies with 1.319 participants met inclusion criteria. Five studies examined adults, four children, and two adolescents. Insecure and unresolved attachment were consistently linked to higher psychological distress, particularly PTSD, especially in adults. In children, insecure attachment was associated with parental mental health problems and dysfunctional parenting, whereas secure attachment buffered the effects of parental PTSD. Discussion: Limitations include small sample sizes, cultural and linguistic complexity, inconsistent definitions of “refugee”, and varied assessment methods. Conclusions: Attachment insecurity is strongly associated with psychological distress in refugees, mirroring patterns in Western clinical populations. Findings support the integration of attachment-informed approaches into refugee mental health care. Funding: This review was funded by the Köhler Stiftung and registered in PROSPERO (CRD42024590759).